Successful implementation of a trans-jurisdictional, primary care, anticipatory care planning intervention for older adults at risk of functional decline: interviews with key health professionals - Dagmar Anna S. Corry; Gillian Carter; Frank Doyle; Tom Fahey; Patrick Gillespie; Kieran McGlade; Peter O'Halloran; Nina O'Neill; Emma Wallace; Kevin Brazil (BMC, 2021)
Abstract Background Aging populations present a challenge to health systems internationally, due to the increasing complexity of care for older adults living with functional decline. This study aimed to elicit expert views of key health professionals on effective and sustainable implementation of a nurse-led, person-centred anticipatory care planning (ACP) intervention for older adults at risk of functional decline in a primary care setting. Methods We examined the feasibility of an ACP intervention in a trans-jurisdictional feasibility cluster randomized controlled trial consisting of home visits by research nurses who assessed participants' health, discussed their health goals and devised an anticipatory care plan following consultation with participants' GPs and adjunct clinical pharmacist. As part of the project, we elicited the views and recommendations of experienced key health professionals working with the target population who were recruited using a 'snowballing technique' in cooperation with older people health networks in the Republic of Ireland (ROI) and Northern Ireland (NI), United Kingdom [n = 16: 7 ROI, 9 NI]. Following receipt of written information about the intervention and the provision of informed consent, the health professionals were interviewed to determine their expert views on the feasibility of the ACP intervention and recommendations for successful implementation. Data were analyzed using thematic analysis. Results The ACP intervention was perceived to be beneficial for most older patients with multimorbidity. Effective and sustainable implementation was said to be facilitated by accurate and timely patient selection, GP buy-in, use of existing structures within health systems, multidisciplinary and integrated working, ACP nurse training, as well as patient health literacy. Barriers emerged as significant work already undertaken, increasing workload, lack of time, funding and resources, fragmented services, and geographical inequalities. Conclusions The key health professionals perceived the ACP intervention to be highly beneficial to patients, with significant potential to prevent or avoid functional decline and hospital admissions. They suggested that successful implementation of this primary care based, whole-person approach would involve integrated and multi-disciplinary working, GP buy in, patient health education, and ACP nurse training. The findings have potential implications for a full trial, and patient care and health policy. Trial registration Clinicaltrials.gov, ID: NCT03902743 . Registered on 4 April 2019.